(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
The essence and content of historical thinking, its historical development, etc. are revealed in the article. Also, the issue of historical thinking being a component of historical-philosophical heritage and its integral relationship with social-philosophical heritage is highlighted.